Rural school in the Tenza Valley, rural education and agroecology reflections on rural “development” - Mejia Alfonso Miguel Fernando (Agronomía Colombiana, 2011)
<span style="line-height: 115%; font-family: ";Arial";,";sans-serif";; font-size: 10pt; mso-fareast-font-family: MinionPro-Regular; mso-fareast-language: EN-US; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> The municipality of Sutatenza (Boyaca), constitutes an important reference for rural education in Colombia due to “Radio Sutatenza” (Educational Radio) and the People’s Cultural Action in the mid-twentieth century. Currently, in the same town, a process called the Campesina Community School del Valle de Tenza has been brewing, under an agroecological approach, guided in its work to the cultural and productive Andean farmers, their families and their young people to cultivate in them a return the field. This article addresses this educational experience for contrasting approaches of “development” with the perceptions and visions that emerge from the rural world, without being radically different, it raises important questions for the call for and controversy of development, from the local.